Censorship detected in MM (Myanmar) - Voidly (2026)
CRITICAL severity censorship detected in Myanmar. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: MM-2026-1964
Keywords: censorship; MM; censorship; critical